EDS SECURITY RULES: PROTECTION AGAINST FRAUD - Muminova, Sunbula Shaxzodovna (Educational Research in Universal Sciences, 2023)
This article analyzes current trends that determine the increase in the number of fraudulent actions involving the use of an electronic digital signature in the structure of crime in the Republic of Uzbekistan, as well as the features of the mechanism for committing such crimes. Moreover, the issues of protecting electronic digital signatures from such cases of fraud are considered.